1995
DOI: 10.1161/01.cir.92.9.287
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Complications After Fontan Operations

Abstract: Thromboembolic complications occur frequently after the Fontan operation and its modifications and are a cause of significant morbidity. The time of presentation varies greatly. The rate of thrombosis appears to be similar in all modifications of the Fontan operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
4
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(183 citation statements)
references
References 22 publications
3
171
4
5
Order By: Relevance
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we noted that many studies have a relatively short follow‐up period in detecting VTE. With those studies with an extended follow‐up period beyond the acute hospital stay,23, 44, 45, 46, 49, 59, 71 symptomatic VTE continued to occur. Hence, future cohort studies and RCTs on VTE after cardiac surgery should consider VTE events well beyond the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Jahangiri et al 183 found a 1.7% incidence (1 in 57 cases) of stroke among patients surviving Fontan procedures, and the stroke occurred in a patient who was being treated with warfarin at a therapeutic level at the time of the stroke. Rosenthal et al 184 reported cerebral thromboembolic events in 4.2% (3 of 70 patients) in another retrospective single-center cohort study of patients surviving Fontan procedures and followed up for a median of 5 years postoperatively. In a more recently published study, Barker et al 185 retrospectively reviewed 402 children who underwent Fontan procedures between 1975 and 1998 for single-ventricle defects and were followed up for a median of 3.5 years postoperatively.…”
Section: Stroke After the Fontan Operationmentioning
confidence: 99%
“…When reported, there appears to be a higher risk within the perioperative period up to 3 to 12 months after Fontan, followed by a lower and constant level of risk, which then increases at 5 to 10 years after Fontan. 184,266,267 There may be some utility to matching the need for and degree of anticoagulation therapy to the magnitude of risk with the recognition that the risk may change over time. Patients who have had previous thrombosis or related events are at high risk for recurrence.…”
Section: Long-term Anticoagulation In the Patient With A Palliated Simentioning
confidence: 99%
“…The prevalence of thrombosis after Fontan palliation is reportedly 1-33%, with a high, immediate risk of thrombosis after surgery and an increased risk for Fontan patients surviving into adulthood (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The anticoagulation regimens for these patients vary (3,11).…”
Section: Introductionmentioning
confidence: 99%